2018
DOI: 10.24966/fsn-1076/100033
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Dietary Behavior of Arab International Students in the US

Abstract: The aim of this study was to examine changes in dietary habits among males, females, single, and married Arab international students in the United States (US). The second aim was to examine differences in food consumption patterns and lifestyle behaviors among these groups. Methods A cross-sectional survey of eating habits before and after moving to the US, recruited Arab international college students (n=95, mean age 25.6±5.6 years old) who has been residing for ≥6 months, in Northeast Ohio (2010). Independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…International students, on the other hand, faced various barriers when it came to maintaining healthy eating habits. These barriers included the high cost of traditional foods compared to fast food options, the poor quality of regular food choices, lack of time and knowledge required for food preparation, challenges related to food preparation methods, taste, appearance, and neophobia, which is the fear of trying new foods [ 49 , 50 , 51 ]. Additionally, religious orientations can affect their access to specific ethnic cuisines such as Arabic, Japanese, or Chinese food.…”
Section: Discussionmentioning
confidence: 99%
“…International students, on the other hand, faced various barriers when it came to maintaining healthy eating habits. These barriers included the high cost of traditional foods compared to fast food options, the poor quality of regular food choices, lack of time and knowledge required for food preparation, challenges related to food preparation methods, taste, appearance, and neophobia, which is the fear of trying new foods [ 49 , 50 , 51 ]. Additionally, religious orientations can affect their access to specific ethnic cuisines such as Arabic, Japanese, or Chinese food.…”
Section: Discussionmentioning
confidence: 99%
“…This includes the consumption of prepared and fast food, which is high in calories and low in nutritional value [ 20 23 ]. For example, Kh Al-Farhan et al [ 24 ] showed that Arabic students, after living in the United States for more than 6 months, tend to develop an eating behavior that is less traditional and more westernized. Sastre and Haldeman [ 25 ] describe a rapid dietary acculturation among adolescent refugees migrated to North Carolina, with an increase in consumed sugary and fast food.…”
Section: Introductionmentioning
confidence: 99%